Optimalisasi Audit Internal dalam Menjamin Keamanan Aset Persediaan Melalui Penguatan Pengendalian Internal dan Deteksi Fraud - Febriyanti Febriyanti; Nailah Cantika A.P.M; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study discusses the optimization of internal audits in ensuring inventory asset security through strengthening internal controls and fraud detection, given that the risks of loss, misuse, and inaccurate recording can cause significant losses to the company. The research method uses a descriptive qualitative approach with literature studies and secondary document analysis from journals, books, official reports, and relevant previous research articles to obtain a conceptual and empirical overview. The results and discussion show that structured and systematic internal audits, which include risk-based planning, control testing, routine and surprise stock counts, segregation of duties, use of information technology, and follow-up on recommendations, play a significant role in preventing inventory fraud, improving recording accuracy, and strengthening internal control systems. In conclusion, the integration of internal audit and internal control provides double protection against the risk of inventory asset misuse, strengthens governance, accountability, and risk management reliability, making it a crucial strategy in maintaining the security of company assets.